Metode Algoritma Genetika dengan Sistem Fuzzy Logic untuk Penentuan Parameter Pengendali PID - Bhakti Yudho Suprapto; . Sariman (Universitas Syiah Kuala, 2012)
Proportional-Integral-Derivative ( PID) represents the popular controller which is frequently used in industry and instrumentation equipments. Although in simple design procedure, tuning of PID parameters ( Kp, KiAnd Kd) to get the optimal value is not easy and simple. Genetic Algorithm method with the Fuzzy Logic system is used to get the PID parameters with optimal performance result. Genetic Algorithm is a method that used to solve a problem of optimization based on selection and genetic evolution, while system of fuzzy logic is used to determine the geneticparameter like crossover probability and mutation. In this research, Genetic Algorithm with the Fuzzy Logic system is forming model of direct-current motor to get the parameters of PID controller based on value of mean square error ( MSE). This Examination yielded the stable response system with the value MSE gyrate 0.0027 until 0.0028 and steady state error gyrate 0.004 until 0.001.